VITAMIN D LEVEL IN COMPLEX ADMINISTRATION OF BRONCHIAL ASTHMA IN CHILDREN - Omonovna, Turayeva Nafisa; Azizovna, Khamzaeva Kamina (Research Focus International Scientific Journal, 2026)
Purpose of study: to evaluate the clinical efficacy of vitamin D supplementation in the complex treatment of bronchial asthma in children. Materials and methods: the study involved 60 children with bronchial asthma. Of these, 13 (21.6%) had a severe persistent form of asthma (group I), 33 (55%) had a moderate form (group II), and 14 (23%) children were observed with a mild persistent form (group III). One of the criteria for participation in the study was the absence of conditions requiring intensive care. The control group consisted of 50 children with moderate acute obstructive bronchitis and no history of allergic diseases. Informed parental consent was obtained for all study participants. The level of the metabolite 25(OH)D in the blood of children was used to analyse vitamin D status. Results and discussion: the concentration of vitamin D (25(OH)D) in the blood serum was assessed before and after treatment using an enzyme immunoassay. According to the recommendations of the US Institute of Medicine, a 25(OH)D level below 20 ng/ml indicates deficiency and 21–30 ng/ml indicates insufficiency. Conclusions: the combination of basic therapy and vitamin D has demonstrated effectiveness, reducing the risk of asthma exacerbations. The inclusion of vitamin D in complex treatment has a positive effect on the course of the disease and its dynamics, which helps to improve treatment and prevention measures.